Comparação das estimativas de prevalência de indicadores de saúde no Município de Campinas, São Paulo, Brasil, nos anos de 2001/2002 (ISA-SP) e 2008/2009 (ISA-Camp) - Francisco, Priscila Maria Stolses Bergamo (2013)
The aim of the study was to compare prevalence estimates of health indicators for adults living in Campinas, São Paulo State, using data from two household surveys (ISA-SP 2001-2002 and ISA-Camp 2008-2009), analyzing data from 941 and 2,637 individuals 18 years and older, respectively. Socio-demographic variables were used to characterize the study population. Prevalence rates and 95% confidence intervals were estimated, and comparisons were performed by prevalence ratios adjusted for sex, age, and education, obtained by Poisson regression with robust variance. Statistically significant differences were observed for prevalence of morbidity, medication, smoking, and lifetime Pap smear and mammogram. Surveillance of health indicators by repeated surveys in the same population can facilitate monitoring goals and objectives by providing support to plan public health interventions.